2020
DOI: 10.1002/jia2.25576
|View full text |Cite
|
Sign up to set email alerts
|

The HIV drug optimization agenda: promoting standards for earlier investigation and approvals of antiretroviral drugs for use in adolescents living with HIV

Abstract: Introduction Most clinical trials for new antiretroviral (ARV) agents are conducted among narrowly defined adult populations. Only after safety and efficacy have been clearly demonstrated among adults living with HIV are trials including adolescents, children and infants conducted. This approach contributes to significant delays in the availability of optimal new ARV regimens for infants, children and adolescents. This commentary discusses issues related to the inclusion of adolescents aged 12 to 18 years in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(25 reference statements)
0
3
1
Order By: Relevance
“…The most common type of failure was virological failure, followed by clinical and immunological failure. These results were greater than those reported for the different regions of Ethiopia, including Addis Ababa (14.1%) [21], the Amhara Regional State (12.19%) [20], and Jimma University Hospital (11.5%) [22]; moreover, the pooled prevalence of treatment failure was 15.3% [22]. Moreover, ART treatment failure among children reported in other parts of Ethiopia, including University of Gondar Hospital (18.2%), [23] Black Lion Hospital (22.6%) [24], and Fiche and Kuyu Hospitals (18.9%) [23], is consistent with these ndings.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The most common type of failure was virological failure, followed by clinical and immunological failure. These results were greater than those reported for the different regions of Ethiopia, including Addis Ababa (14.1%) [21], the Amhara Regional State (12.19%) [20], and Jimma University Hospital (11.5%) [22]; moreover, the pooled prevalence of treatment failure was 15.3% [22]. Moreover, ART treatment failure among children reported in other parts of Ethiopia, including University of Gondar Hospital (18.2%), [23] Black Lion Hospital (22.6%) [24], and Fiche and Kuyu Hospitals (18.9%) [23], is consistent with these ndings.…”
Section: Discussioncontrasting
confidence: 76%
“…This could be because stunted children may have had poorer baseline health and ART compliance than normal children. In reality, HIV affects nutritional status on its own, increasing susceptibility to the virus and hastening disease progression in malnourished children [21,35]. Furthermore, stunted children may have had a simultaneous opportunistic infection that caused them to miss out on receiving their medications [36].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the current study discovered that patients with TB/HIV co-infection who were receiving INH had a 0.310 times lower mortality rate than those who were not receiving INH. Individuals with HIV and drug-susceptible TB should get standard anti-TB therapy, which includes 2 months of isoniazid (INH), rifampin, pyrazinamide, and ethambutol (intensive phase), followed by 4 months of isoniazid (INH) and rifampin (continuation phase) 50 . Studies from various parts of the world reported CPT as a significant predictor of mortality among patients co-infected with TB and HIV.…”
Section: Discussionmentioning
confidence: 99%
“…By 2022, a total of 39.0 million people were living with HIV-1 [ 3 , 4 ]. Current guidelines recommend that people with HIV-1 infection receive antiretroviral therapy (ART) immediately after they are diagnosed [ 5 , 6 ]. ART has improved the survival and quality of life of HIV-1-infected patients, but also poses challenges such as drug resistance, toxicity, and poor adherence [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%